Inheritance of coat colour in the cane Corso Italiano dog - Korec, Evžen; Hančl, Matyáš; Bydžovská, Marie; Chalupa, Ondřej; Korcová, Jana (BMC genetics, 2019)
BACKGROUND: The inheritance of different coat colours in the Cane Corso Italiano dog has not been described thus far. We analysed data from 23,271 dogs and bitches using the Cane Corso Italiano Pedigree Database. We are describing for the first time the coat colour segregation ratios in Cane Corso Italiano offspring arising from crosses between parents of all possible coat colour combinations. RESULTS: Segregation ratios that do not follow a Mendelian pattern suggest that additional genes are active in the determination of coat colour. Segregation ratios of offspring produced by parental crossing (male colour A x female colour B) were compared with the ratios of offspring produced by reciprocal crossing (male colour B x female colour A) in all possible coat colour combinations. Most of the segregation ratios were the same, but some segregation ratios in reciprocal crosses differed. This result suggests that at least one gene responsible for coat colour is located on a sex chromosome. The sex ratio was analysed in the offspring of all colour groups. A ratio of 1:1 was not confirmed in 8 colour groups by the chi-square test. CONCLUSIONS: We described for the first time coat colour segregation ratios in Cane Corso Italiano dogs. Furthermore, we present the hypothesis that at least one gene responsible for coat colour is located on a sex chromosome.
Keywords: mužské pohlaví; zvířecí srst; pigmentace; ženské pohlaví; Animals; zvířata; Male; Female; Dogs; Pigmentation; Animal Fur; psi